Protective role of Lagenaria Siceraria seed oil against furan-induced toxicity: Histopathological, biochemical, and molecular insights in male Albino rats. - Mona Zahran; Fatima S Alaryani; Khlood M El Bohi; Ehsan H Abu Zeid; Mohamed H Khairy; Aishah E Albalawi; Reem H Alhasani; Shatha G Felemban; Reda Korany (PLoS ONE)
This study aimed to assess the protective effects of Lagenaria siceraria seed oil (LSO) on fifty male Albino rats subjected to furan exposure. Furan (FU) is a small, heterocyclic compound present in the volatile fraction of various thermally processed foods and beverages. Rats were categorized into five groups, each comprising ten rats. Group 1 served as the control group, receiving corn oil. Group 2 received LSO (3 g/kg body weight orally) for 28 days. Rats in Group 3 (FU-exposed group) received an oral administration of FU at a dosage of 16 mg/kg body weight each day for 28 days. Rats in Group 4 (Therapeutic co-treated group) were administered both LSO and subsequent FU exposure according to the previously outlined dosage regimen for 28 days. Rats in Group 5 (Protective co-treated group) received LSO seed oil for 14 days as protection then received Fu at the same mentioned doses of Fu until the end of experiment. Rats administered FU and/or LSO gained noticeably more weight than the control group. LSO significantly decreased AST and LDH levels in both the protection and treatment groups as compared to the FU-only group. It also assisted in restoring testosterone and luteinizing hormone (LH) levels that were decreased by FU, especially in the protected group. LSO also reduced kidney damage markers and normalized biomarker levels when administered with FU. The LSO-only group demonstrated normal immune response markers, similar to the control group. By changing MDA levels and increasing SOD, GSH, and TAC levels, co-treatment with LSO enhanced liver health. The control and LSO groups displayed normal spleen structure, whereas the LSO/FU group had normal seminiferous tubules with mild edema and congestion. Overall, LSO demonstrated protective and therapeutic benefits against FU-induced damage in rats.